The Quality of Organic Waste Market Ensiled Using Rejected Commercial Syrup as an Alternative Ruminant Livestock Feed - Sadarman, Sadarman; Febrina, Dewi; Rinaldi, Satria Trisna; Hendri, Hendri; Ichwan Ilyazar, Mohammad; Weno, Weno; Alfian, Aldi; Amalia Nurfitriani, Rizki; Qomariyah, Novia; Sukmara, Anne; Koswara, Eko; Prihambodo, Tri Rachmanto; Gholib, Gholib; Faiz Mohd Azmi, Amirul (Faculty of Animal Science, Jenderal Soedirman University in associate with the Animal Scientist Society of Indonesia (ISPI) and the Indonesian Association of Nutrition and Feed Science (AINI), 2023)
Market organic waste (LOP) is organic residue or residue generated from market trading activities such as residual vegetables, fruits, and other organic foodstuffs. This waste can be a source of environmental problems if not managed properly because it can rot and cause unpleasant odors. Still, if managed properly, it can be used as an alternative feed for livestock. This study aims to evaluate the quality of LOP silage using rejected commercial syrup as silage additives. The manufacture, harvesting, drying, and siege of silage are conducted at the Laboratory of Nutrition and Feed Technology, Faculty of Agriculture and Animal Husbandry, Sultan Syarif Kasim State Islamic University, Riau. The experimental method with a Complete Randomized Design consisting of 5 treatments and five repeats was used in this study. The treatment in question was P1: spinach 33.3% + cabbage 33.3% + kale 33.3% as control, for P2, P3, P4, and P5 plus SKA of 1%, 2, 3, and 4%, respectively, based on dry matter, then enzymatic for 30 days at room temperature. The parameters measured are temperature, humidity, mold growth, and silage pH. The data obtained were analyzed based on variety analysis, and the difference in parameter values between treatments was further tested with a DMRT level of 5%. The results of the variety analysis showed that the use of SKA had a significant effect (P<0.05) on temperature, humidity, fungal growth, and silage pH. The silage temperature at the time of harvesting averages 30±0.39°C; the average humidity is 77±0.25%; mushroom growth averaged 2.87±0.39%; and an average silage pH of 3.67±0.45. The conclusion is that SKA can improve the quality of market organic waste silage by optimizing temperature and humidity during ensilage to minimize pH and mold growth.